Improvement of Mechanical, Thermal and Optical Properties of Barium Mixed Cobalt Tartrate Hydrate Crystals Grown by Gel Method - S. Vanaja; V. Selvamurugan; P.V. Chandrasekar; R. Krishna Sharma; M. Alagar (Журнал нано- та електронної фізики)
In this present work, CTH and BCTH crystals have been prepared by gel technique by using single diffusion method at room temperature. The as grown crystals were characterized by using XRD, FT-IR, UV, TG / DTA and Micro hardness studies. X-ray powder diffraction results analyzed by using suitable software suggest that a CTH and BCTH crystals belong to cubic crystal system. The unit cell volume is observed to increase with increase in the concentration of barium in cobalt tartrate due to the lattice distortion. The band gap and optical properties have analyzed by UV-Visible spectrum. The functional groups and compound formation of the crystals have been studied by FT-IR spectrum. The mechanical properties of the grown crystals were tested by using Vicker’s microhardness studies. The work hardening coefficient (n) was determined to be 3.7 for CTH, 5.3 for BCTH (1 : 1) and 6.4 for BCTH (2 : 1) and the stiffness constants for different loads were calculated and reported. Thermal analysis suggests that pure cobalt tartrate starts decomposing at 73.2 °C whereas the barium mixed cobalt tartrate brings about better thermal stability which increases with an increase in barium concentration.